THE MISTAKES AND SHORTCOMINGS OF BLIND AND VISUALLY IMPAIRED INDIVIDUALS IN LANGUAGE LEARNING (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
This article explores the common mistakes and shortcomings of blind and visually impaired individuals during language learning. The unique challenges this demographic faces are examined, focusing on the limitations in accessing visual aids, written materials, and traditional classroom methods that rely on sight-based teaching. Furthermore, the paper highlights the importance of tactile and auditory tools, alternative communication methods, and inclusive teaching strategies that can enhance language acquisition for these learners. Practical solutions, including the use of braille, screen readers, and adaptive technology, are also discussed. The article emphasizes the need for individualized learning plans and specialized teacher training to cater to the specific needs of visually impaired students in language education.